2016
DOI: 10.1186/s12917-016-0730-8
|View full text |Cite
|
Sign up to set email alerts
|

Toxin-neutralizing antibodies protect against Clostridium perfringens-induced necrosis in an intestinal loop model for bovine necrohemorrhagic enteritis

Abstract: BackgroundBovine necrohemorrhagic enteritis is caused by Clostridium perfringens type A. Due to the rapid progress and fatal outcome of the disease, vaccination would be of high value. In this study, C. perfringens toxins, either as native toxins or after formaldehyde inactivation, were evaluated as possible vaccine antigens. We determined whether antisera raised in calves against these toxins were able to protect against C. perfringens challenge in an intestinal loop model for bovine necrohemorrhagic enteriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
1
27
0
1
Order By: Relevance
“…A recent study has shown that although formaldehyde inactivated alpha toxin vaccines stimulated antibody production similar to native alpha toxin vaccines, only antibodies produced from the native toxin vaccines provided protection in an intestinal loop assay. 105 Recombinant vaccines may offer advantages compared with conventional toxoid vaccines in the future. 106 C perfringens vaccination strategies based on species, age, and animal use are provided in Table 3.…”
Section: Prevention Vaccinationmentioning
confidence: 99%
“…A recent study has shown that although formaldehyde inactivated alpha toxin vaccines stimulated antibody production similar to native alpha toxin vaccines, only antibodies produced from the native toxin vaccines provided protection in an intestinal loop assay. 105 Recombinant vaccines may offer advantages compared with conventional toxoid vaccines in the future. 106 C perfringens vaccination strategies based on species, age, and animal use are provided in Table 3.…”
Section: Prevention Vaccinationmentioning
confidence: 99%
“…However, situations of imbalance with an exacerbated proliferation of this bacterium are associated with diseases of the digestive tract. C. perfringens is a toxinogenic bacterium and its classification can be made according to the pattern of toxin production in type A, B, C, D, and E strains (Morris et al 2012, Allaart et al 2013, Verherstraeten et al 2013, Goossens et al 2016b, 2017. Isolation and genotyping of bacteria in the intestinal contents and feces of animals of this report evidenced only type A strains.…”
Section: Discussionmentioning
confidence: 75%
“…animals (Lebrun et al 2010, Verherstraeten et al 2013, Goossens et al 2016a, 2016b, 2017. Although this disease presents a low morbidity and individual cases are observed sporadically, the high lethality, the rapid course to death, and the almost impracticable treatment confer economic importance to this disease in cases of outbreak, and prophylaxis should be prioritized (Lebrun et al 2010, Goossens et al 2016a, 2016b, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…All C. perfringens can secrete alpha‐toxin (CPA). As the most important exotoxin of C. perfringens , alpha‐toxin is a powerful necrosis factor, researchers have regarded it as the most important research object in recent years (Goossens et al, , , ; Siqueira et al, ; Takehara, ). Alpha‐toxin is a multifunctional metalloenzyme with phospholipase C (PLC) and sphingomyelinase (SMase) enzyme activities that simultaneously hydrolyse phosphatidylcholine and sphingomyelin (Goossens et al, ; Nagpal et al, ; Uzal et al, ).…”
Section: Introductionmentioning
confidence: 99%